Subprime borrowers, securitization and the transmission of business cycles - Anna Grodecka (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
One of the roots of the recent global financial crisis has been seen in the design of subprime mortgage contract leading to high sensitivity of such type of loans to house price changes. The market of subprime loans, especially in the last years preceding the crisis, has been highly financed by securitization. The paper investigates how borrowers with subprime characteristics influence the transmission mechanism of business cycles in the economy and whether the securitization of subprime loans has a positive effect on the economy. The formal setup is a DSGE model with different types of borrowers and banks acting as financial intermediaries, in which households and entrepreneurs borrow against housing collateral. The economy is subject to four shocks: monetary, inflationary, preference and technology. It is shown that alone the existence of subprime borrowers does not make the economy more responsive to different shocks at the aggregate level (it has only redistributional effects) and that under certain circumstances the securitization of subprime loans (in form of residential mortgage backed securities) may lead to amplification of the business cycles.
Keywords: E32; E44; G21; 330